Estrone Sulfate Transport and Steroid Sulfatase Activity in Colorectal Cancer: Implications for Hormone Replacement Therapy - Gilligan, Lorna C.; Gondal, Ali; Tang, Vivien; Hussain, Maryam T.; Arvaniti, Anastasia; Hewitt, Anne-Marie; Foster, Paul A. (Frontiers in Pharmacology, 2017)
Hormone replacement therapy (HRT) affects the incidence and potential progression of colorectal cancer (CRC). As HRT primarily consists of oestrone sulphate (E1S), understanding whether this conjugated oestrogen is transported and metabolised in CRC will define its potential effect in this malignancy. Here we show that a panel of CRC cell lines (Colo205, Caco2, HCT116, HT-29) have steroid sulphatase (STS) activity, and thus can hydrolyse E1S. STS activity is significantly higher in CRC cell lysate, suggesting the importance of E1S transport in intracellular STS substrate availability. As E1S transport is regulated by the expression pattern of certain solute carrier organic anion transporter polypeptides (SLCO/OATP), we show that in CRC OATP4A1 is the most abundantly expressed transporter. All four CRC cell lines rapidly transported E1S into cells, with this effect significantly inhibited by the competitive OATP inhibitor BSP. Transient knockdown of OATP4A1 significantly disrupted E1S uptake. Examination of oestrogen receptor status showed ER was present in Colo205 and Caco2 cells. None of the cells expressed ER. Intriguingly, HCT116 and HT29 cells strongly expressed the G protein coupled oestrogen receptor (GPER), and that stimulation of this receptor with oestradiol (E2) and G1, a GPER agonist, significantly (p < 0.01) increased STS activity. Furthermore, tamoxifen and fulvestrant, known GPER agonist, also increased CRC STS activity, with this effect inhibited by the GPER antagonist G15. These results suggest that CRC can take up and hydrolyse E1S, and that subsequent GPER stimulation increases STS activity in a potentially novel positive feedback loop. As elevated STS expression is associated with poor prognosis in CRC, these results suggest HRT, tamoxifen and fulvestrant may negatively impact CRC patient outcomes.